Conversion of glucose into 5-hydroxymethylfurfural on Ukrainian natural zeolites - Patrylak, Lyubov K.; Konovalov, Serhiy V.; Zubenko, Stepan O.; Yakovenko, Anzhela V.; Voloshyna, Yuliya G.; Pertko, Olexandra P. (V.P. Kukhar Institute of Bioorganic Chemistry and Petrochemistry of the National Academy of Sciences of Ukraine, 2025)
An important product of biomass carbohydrate conversion is 5-hydroxymethylfurfural as a potential raw material component of a wide range of important chemicals. The aim of the work was to study the conversion of glucose into 5-hydroxymethylfurfural in the presence of modified clinoptilolite and mordenite-clinoptilolite zeolite rocks from Transcarpathia. A number of acid catalysts have been synthesized by liquid-phase ion exchange of native cations with calcium, lanthanum, and ammonium cations, as well as by dealumination with hydrochloric and ethylenediaminetetraacetic acid. Their properties were characterized using XRD and XRF analysis, low-temperature nitrogen adsorption/desorption, and FTIR spectroscopy. The acidity of the samples was determined by reverse n-butylamine titration. Acid treatment of the samples contributed to an increase in the specific surface area of the samples by an order of magnitude. The samples were tested in the conversion of 9% aqueous glucose solution into 5-hydroxymethylfurfural. The composition of the reaction products was analyzed by gas chromatography. The glucose conversions and the yields of 5-hydroxymethylfurfural, levulinic acid, and fructose were calculated. The glucose conversions ranged from 30 to 70 %. The results were analyzed in accordance with the characteristics of the nature of the active sites of the catalysts and the porous structure of the latter. It was found that the samples with the presence of Lewis acid sites in the form of extra-framework aluminum and multiply charged cations are characterized by the highest 5-hydroxymethylfurfural yields. Due to glucose conversion occurs mainly on the outer surface of zeolite crystals and at the entrances to the cavities, the polycationic form of clinoptilolite, despite its low porous characteristics, demonstrates the highest yield of 5-hydroxymethylfurfural.